Sharing Aggregate Inventory Information with Customers: Strategic Cross-Selling and Shortage Reduction - Cui, Ruomeng; Shin, Hyoduk (Management Science, 2018)
This paper studies the strategy of sharing inventory information for a firm that sells two vertically differentiated products. The seller has private information on the aggregate inventory level and the inventory composition of two product variants. The seller credibly and discretionarily discloses inventory information to customers either fully or partially, i.e., disclosing the exact inventory of each product variant, the aggregate inventory level, or no information to customers. Customers form expectations of future availability and make rational purchasing decisions accordingly. In the disclosure literature, discretion usually leads to an unraveling result: sellers who learn favorable market information opt to disclose it, making full disclosure the equilibrium. This paper shows that aggregate inventory disclosure, i.e., partial disclosure, can be instead sustained as an ex post equilibrium. We demonstrate that inventory information aggregation arises when there is an ex post desire to reduce supply–demand mismatches in all inventory scenarios. Specifically, when customers’ preferred products are more likely to stock out, the seller could entice more incoming consumers who hope that their desired products are in stock by withholding product composition but disclosing the aggregate inventory level. If customers’ desired products are sold out, the seller can benefit from upselling or cross-selling customers’ less preferred products. Alternatively, when the seller stocks more desired products, aggregate disclosure can dampen the flow of incoming customers and reduce the shortage penalty cost. This result is robust under various settings: risk-averse customers, heterogeneous customers, and horizontally differentiated products. This paper was accepted by Serguei Netessine, operations management.